2017
DOI: 10.18203/2320-6012.ijrms20174960
|View full text |Cite
|
Sign up to set email alerts
|

Structured teaching programme on knowledge about polycystic ovarian syndrome among adolescent girls

Abstract: Background: Polycystic ovarian syndrome is a common female endocrine disorder affecting 4 – 18% of women in their reproductive age. It is common in adolescent girls. Polycystic Ovarian Syndrome affects throughout the life and produce gynaecological and metabolic health problems. The aim of this study to create the awareness about the polycystic ovarian syndrome to the adolescent girls.Methods: A Quantitative approach with pre- experimental design was used to study the effectiveness of STP on Poly Cystic Ovaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…The present result is supported by Mohamed [13] who studied effect of educational program on the level of knowledge regarding polycystic ovarian syndrome among adolescent girls and stated that there is a highly statistically significant improvement in students' knowledge immediately after program implementation. In the same line, the current study is supported by Rawat, et al, [17] who reported that, the mean post-test score was higher than that the pre-test mean knowledge score after intervention.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The present result is supported by Mohamed [13] who studied effect of educational program on the level of knowledge regarding polycystic ovarian syndrome among adolescent girls and stated that there is a highly statistically significant improvement in students' knowledge immediately after program implementation. In the same line, the current study is supported by Rawat, et al, [17] who reported that, the mean post-test score was higher than that the pre-test mean knowledge score after intervention.…”
Section: Discussionsupporting
confidence: 86%
“…There is a need to increase awareness among students and improve their lifestyle behaviors to avoid major problems in the future. [17] Aim of the Study: To evaluate the educational program and its effect on knowledge and lifestyles among paramedical students with polycystic ovarian syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…7 In contrast, Rawat et al during a study among adolescent girls in Dehradun found that only 1.06% participants had knowledge on PCOS. 8 Also, study conducted by Jena et al in the Department of Obstetrics and Gynecology, All India Institute of Medical Sciences (AIIMS), Bhubaneswar reported only 2.79% and by Sharma et al among rural and urban population of Punjab indicated only 3.30% participants knew about the disease. 9 10 Chainani did a survey in D.Y.…”
Section: Discussionmentioning
confidence: 98%
“…7 In contrast, Rawat et al during a study among adolescent girls in Dehradun found that only 1.06% participants had knowledge on PCOS. 8 Another study carried in gynecology outpatient department at a tertiary care hospital by Kaundal revealed 43.4% females heard about PCOS. 13 Salama and Elbana at Nursing Institute of Benha Teaching Hospital and Nursing Institute of Health Insurance Hospital, Egypt revealed that most of the adolescents had inadequate knowledge and only 6.3% of studied population had adequate knowledge.…”
Section: Discussionmentioning
confidence: 98%
“…Insulin resistance is central to the pathogenesis of PCOS (8) Indians are known to have high prevalence of insulin resistance, so the prevalence of PCOS is expected to be high in the Indian population (9) . The short complications of polycystic ovarian disease include menstrual irregularities, hyperandrogenism, insulin resistance and hyperinsulimia, obstructive sleep apnea, dyslipidemia, oligoovulation anovulation and the longterm complications includes endometrial hyperplasia, metabolic syndrome, cardiovascular disease and psychological disorders.…”
Section: Introductionmentioning
confidence: 99%